Afghanistan: Quest for Peace and Stability (Historical Context) - Iram Khalid (Journal of Political Studies, 2011)
In the politico-strategic perspective, Afghanistan is considered one of the most difficult and challenging countries in the world. Its fragmented society is a major hurdle in the way of its nation building and state formation. With its multi-ethnic and multi-linguistic groups, it is a complicated country on the global map. In this situation, it can be imagined that the internal peace is linked with the lowest credibility of the Afghan warlords, unpopular and corrupt leadership, and the centuries old traditional legacy. Resistance against the social and political order has remained the core feature of Afghan society. Throughout its history, several internal and external players have been involved in their game of interest. Now-a-days, these warlords are involved in tactical and vicious alliances due to which they have lost their ideological reasoning. This paper is an attempt to critically analyze the situation of this country and to present an insight of the overall situation.